2015
DOI: 10.3325/cmj.2015.56.114
|View full text |Cite
|
Sign up to set email alerts
|

ATP-sensitive potassium channels modulate in vitro tocolytic effects of β2-AR agonists on uterine muscle rings in rats in early but not in late pregnancy

Abstract: AimTo investigate whether ATP-sensitive potassium (KATP) channels modulate the tocolytic effect of β2-AR agonists (ritodrine and salmeterol) in early-pregnant (day 6) and late-pregnant (day 22) rat uterus in vitro, in order to examine the relation between the KATP channel sulphonylurea-binding regulatory subunit (SUR) expression and pharmacological reactivity of β2-AR agonists.MethodsThe tocolytic effects of ritodrine and salmeterol (10-10-10-5 M) on spontaneous rhythmic contractions were investigated cumulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Ritodrine hydrochloride is a beta-2-adrenergic receptor highly selective for the uterine smooth muscles. 14 Although its high selectivity for the uterine muscle suggests that it would cause milder stimulation to the heart muscle as compared to other adrenergic drugs, most pregnant women in whom ritodrine is administered experience some symptoms, such as palpitations, chest distress, or chest pain. Pregnant women may dismiss painful symptoms as a normal part of pregnancy and birth, especially to prevent preterm delivery of their fetuses, and may not report such symptoms to their physician.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ritodrine hydrochloride is a beta-2-adrenergic receptor highly selective for the uterine smooth muscles. 14 Although its high selectivity for the uterine muscle suggests that it would cause milder stimulation to the heart muscle as compared to other adrenergic drugs, most pregnant women in whom ritodrine is administered experience some symptoms, such as palpitations, chest distress, or chest pain. Pregnant women may dismiss painful symptoms as a normal part of pregnancy and birth, especially to prevent preterm delivery of their fetuses, and may not report such symptoms to their physician.…”
Section: Discussionmentioning
confidence: 99%
“…Ritodrine hydrochloride is a beta‐2‐adrenergic receptor highly selective for the uterine smooth muscles 14 . Although its high selectivity for the uterine muscle suggests that it would cause milder stimulation to the heart muscle as compared to other adrenergic drugs, most pregnant women in whom ritodrine is administered experience some symptoms, such as palpitations, chest distress, or chest pain.…”
Section: Discussionmentioning
confidence: 99%
“…Low expression of the K ATP channels at the end of gestation may facilitate enhanced excitability and contractility in the rat myometrium [27]. The mechanism/s of the relaxant effect of apelin proved in the present study are supported by the study of Yang et al [28] who demonstrated that apelin binds with APJ leading to increased Ca 2+ influx that will lead to activation of NOS , phospholipase A 2 and increased release of endothelial derived hyperpolarizing factor (EDHF) which induces smooth muscle relaxation .…”
Section: Discussionmentioning
confidence: 99%